Henri Bergson - Jankelevitch, Vladimir (Duke University Press, 2015)
Appearing here in English for the first time, Vladimir Jankélévitch's Henri Bergson is one of the two great commentaries written on Henri Bergson. Gilles Deleuze's Bergsonism renewed interest in the great French philosopher but failed to consider Bergson's experiential and religious perspectives. Here Jankélévitch covers all aspects of Bergson's thought, emphasizing the concepts of time and duration, memory, evolution, simplicity, love, and joy. A friend of Bergson's, Jankélévitch first published this book in 1931 and revised it in 1959 to treat Bergson's later works. This unabridged translation of the 1959 edition includes an editor's introduction, which contextualizes and outlines Jankélévitch's reading of Bergson, additional essays on Bergson by Jankélévitch, and Bergson's letters to Jankélévitch